2006
DOI: 10.1007/s00421-005-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Facial cold-induced vasodilation and skin temperature during exposure to cold wind

Abstract: One purpose of this study was to characterize the facial skin temperature and cold-induced vasodilation (CIVD) response of 12 subjects (six males and six females) during exposure to cold wind (i.e., -10 to 10 degrees C; 2, 5, and 8 m/s wind speed). This study found that at each wind speed, facial skin temperature decreased as ambient temperature decreased. The percentage of subjects showing facial CIVD decreased significantly at an ambient temperature above -10 degrees C. A similar CIVD percentage was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…However, if conditions are windy, physical activity does not significantly alter the temperature of exposed or covered fingers. Exposure to a 5 m⋅s −1 wind at an ambient temperature of −10 • C when performing light to moderate physical activity only raises the finger temperature in a glove from 10 • C at rest to ∼13 • C. However, increasing the exercise intensity from 220 to 350 Watts increases nose temperatures from 4.5 to 8.9 • C, even in a 5 m⋅s −1 wind (26,97) and Brajkovic and Ducharme (26) found that nose skin temperature rose from 9.7 • C at rest to 18.1 • C during exercise.…”
Section: Cold Air Exposurementioning
confidence: 96%
“…However, if conditions are windy, physical activity does not significantly alter the temperature of exposed or covered fingers. Exposure to a 5 m⋅s −1 wind at an ambient temperature of −10 • C when performing light to moderate physical activity only raises the finger temperature in a glove from 10 • C at rest to ∼13 • C. However, increasing the exercise intensity from 220 to 350 Watts increases nose temperatures from 4.5 to 8.9 • C, even in a 5 m⋅s −1 wind (26,97) and Brajkovic and Ducharme (26) found that nose skin temperature rose from 9.7 • C at rest to 18.1 • C during exercise.…”
Section: Cold Air Exposurementioning
confidence: 96%
“…This cold-induced vasodilatation (CIVD) phenomenon was Wrst reported by Lewis (1930) in the Wngers, and has been presumed to perform a cryoprotective function to maintain tissue integrity and minimize the risk of cold injuries. Since this initial report, the vast majority of CIVD research has been performed on the hands (Daanen 2003), though CIVD has also been observed in the face (Brajkovic and Ducharme 2006), forearm (Ducharme et al 1991), and feet (GreenWeld et al 1951). Few researchers have studied the response of the foot or toes to acute or repeated cold exposures, despite it being the dominant site for actual cold injuries.…”
Section: Introductionmentioning
confidence: 93%
“…With regards to local air exposure, air temperatures ranging from 10 to ¡18°C have been used to cool the Wngers for 2 h in order to induce CIVD (Kramer and Schulze 1948). On the other hand, whole body exposures of 10°C (Montgomery and Williams 1977;Brajkovic and Ducharme 2006), 1°C (Steegmann Jr 1979), 0°C (Shitzer et al 1998a;Brajkovic and Ducharme 2006), ¡7°C (Santee et al 1990), ¡10°C (Brajkovic and Ducharme 2006), and ¡17°C (Shitzer et al 1991(Shitzer et al , 1998bShitzer 1998) lasting up to 2 h have been adopted as CIVDinducing techniques in humans. Experiments in rats have identiWed CIVDs in whole body exposures at ambient temperatures of 5 and 10°C (Berry et al 1984).…”
mentioning
confidence: 99%